Penerapan Sanksi Terhadap Residivis Tindak Pidana Narkotika Dilihat Dari Perspektif Hukum Penitensier - Paruki, Novia Rahmawati A.; Puluhulawa, Fenty U.; Puluhulawa, Jufryanto (CV. ITTC INDONESIA, 2023)
This study aims to find out how the application of narcotics criminal recidivism sanctions is seen from the perspective of penitesnier law and the factors that cause recidivism of narcotics crimes. This study uses empirical legal research methods which are carried out by collecting data through observation and interviews. The results of the research on the Application of Sanctions Against Recidivist Perpetrators of Narcotics Crime Seen from a Penitensier Legal Perspective are not optimal. The application of sanctions against recidivists of narcotics crimes in the perspective of penitential law must include aspects of prevention, rehabilitation, fair treatment and strict supervision. This aims to reduce the level of recidivism, improve the behavior of perpetrators, and prepare for reintegration into society. law enforcement and government. The Application of Sanctions Against Recidivist Perpetrators of Narcotics Crime From the Perspective of Penitensier Law is not optimal. The application of sanctions against recidivists of narcotics crimes in the perspective of penitential law must include aspects of prevention, rehabilitation, fair treatment and strict supervision. This aims to reduce the rate of recidivism, improve the behavior of offenders, and prepare for reintegration into society. Causes of Recidivists Committing Narcotics Crimes are influenced by internal and external factors including: personality, mental health, religion, social and economic skills, environment, social, law enforcement officials and government.